2020
DOI: 10.3389/feduc.2020.00150
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Doctoral Training in Technology-Enhanced Learning in Europe

Abstract: Technology enhanced learning (TEL) research connects Learning Sciences, Educational Psychology, and Computer Science, in order to investigate interventions based on digital technologies in education and training settings. In this paper, we argue that doctoral training activity for TEL needs to be situated at the intersection of disciplines in order to facilitate innovation. For this, we first review the state of disciplinarity in TEL, reviewing existing meta-studies of the field. Then, we survey 35 doctoral ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Doctoral summer schools can be valuable elements contributing to the IJSHE 23,7 careers of doctoral candidates, offering unique opportunities for intersectoral mobility and international collaboration, consistent with the Salzburg Principles on doctoral education (EUA-CDE, 2016). A number of cases have already shown that doctoral summer schools can support participants in developing interdisciplinary and international networks (Pammer-Schindler et al, 2020). In addition to traditional teaching methods, such as lectures, summer schools usually engage students in active learning, through presentations, as well as smalland large-group discussions, where lecturers or teachers act as facilitators.…”
Section: Doctoral Summer Schoolsmentioning
confidence: 99%
“…Doctoral summer schools can be valuable elements contributing to the IJSHE 23,7 careers of doctoral candidates, offering unique opportunities for intersectoral mobility and international collaboration, consistent with the Salzburg Principles on doctoral education (EUA-CDE, 2016). A number of cases have already shown that doctoral summer schools can support participants in developing interdisciplinary and international networks (Pammer-Schindler et al, 2020). In addition to traditional teaching methods, such as lectures, summer schools usually engage students in active learning, through presentations, as well as smalland large-group discussions, where lecturers or teachers act as facilitators.…”
Section: Doctoral Summer Schoolsmentioning
confidence: 99%
“…As a result, the study and use of TEL have gained acceptance in Germany [24], where institutions have started using it heavily in an effort to lessen the effects of COVID-19 [25]. Although TEL has been used in a similar way outside of Europe, little research has been conducted on the subject.…”
Section: Introductionmentioning
confidence: 99%
“…Building upon this perspective, and acknowledging the pivotal role of post-graduate studies in advancing knowledge and its practical applications across diverse domains [2], it becomes imperative to gain insight into the nature of doctoral research. This understanding is vital in assessing its contribution to fostering innovation and knowledge generation, especially in light of the profound impact of digital technologies across various sectors and institutions in society [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…While certain technologies are still in the process of establishing their presence in educational research [10,11], TE has evolved into a significant sub-field within the broader domain of education [8]. A deeper exploration of this sub-field is essential for understanding its subject matter and the prevailing directions in scientific inquiry [5,7]. Research trend analysis is of particular significance.…”
Section: Introductionmentioning
confidence: 99%